ALKALI ALUMINOSILICATE-SATURATED AQUEOUS FLUIDS IN THE EARTH'S UPPER MANTLE - Mysen B.O.; Wheeler K. (My University, 2000)
The solubility in aqueous fluids of peralkaline alkali aluminosilicate components has been determined in the 0.8 to 2.0 GPa and 1000 to 1300°C pressure and temperature range, respectively. Compositions were along the haploandesite join, Na2Si4O9-Na2(NaAl)4O9, with 0, 3, and 6 mol.% Al2O3, denoted NS4Ax, where x represents the mol.% Al2O3.The silicate solubility in aqueous fluid is in the 3 to 20 mol.% range for NS4, 2 to 13 mol.% for NS4A3, and 1.5-8 mol.% for NS4A6 with a linear and positive temperature-dependence and a nonlinear and positive pressure-dependence. The silicate solubility decreases with increasing Al2O3 content. From stepwise regression, the pressure-, temperature-, and Al2O3-dependence of the solubility can be described with the expression: Xsilicate (mol.%)=1.9-1.3XAl2O3 (mol.%)+0.008T(°C)+13P(GPa)+7.3P2. Partial molar volume of H2O in the silicate-saturated fluids, VH2Ofluid, is in the range 17 to 25 cm3/mol. The VH2Ofluid was calculated with the assumption that the activity of dissolved silicate in aqueous fluid equals the mol fraction of dissolved silicate. Compared with the molar volume of pure H2O, V^oH2O, the VH2Ofluid values are 10 to 15% lower at 0.8 GPa and as much as 15% higher than V^oH2O at 2.0 GPa. This volume difference diminishes as the system become more aluminous.For all compositions, the VH2Ofluid is a linear and negative function of pressure with β[= -1/V0(#VH2Ofluid/#P)T] ~ 0.125 GPa-1 for NS4. The βNS4A3 increases from 0.141 to 0.172 in the 1000° to 1300°C range, whereas βNS4A6 increases from 0.193 to 0.213 GPa-1.The VH2Ofluid is a positive and linear function of temperature with thermal expansion coefficients in the range 3-8 x 10-4 K-1. This thermal expansivity resembles that of pure H2O although the exact values and the range in values for pure H2O differ from 1/V0(#VH2Ofluid/#T)P of silicate-saturated aqueous solution.